MEDIASI CONSUMER TRUST DALAM PENGARUH ONLINE CUSTOMER REVIEW DAN FREE SHIPPING PROMOTION TERHADAP PURCHASE DECISION - Miranti, Rina; Susilowati, Heni (Universitas Boyolali, 2025)
The high internet penetration in Indonesia (78.19%) has driven the rapid growth of e-commerce, making platforms like Shopee dominant. Online shopping behavior is strongly influenced by digital stimuli, such as Online Customer Review (OCR) and Free Shipping Promotion. This study aims to analyze the effect of Online Customer Reviews (OCR) and free shipping promotions on purchase decisions in the Shopee marketplace, with trust as an intervening variable. Using a quantitative approach with Structural Equation Modeling (SEM) on data collected from 100 Shopee users in Oku Timur Regency, the results revealed that OCR and free shipping promotions significantly and positively influence both trust and purchase decisions. Trust mediates the relationship between OCR, free shipping promotions, and purchase decisions partially. The model explains 74.4% of the variance in trust and 87.3% of the variance in purchase decisions, indicating strong predictive power. These findings contribute theoretically by elucidating trust as a key mechanism linking digital stimuli to consumer behavior, and practically by aiding marketplace operators and SMEs in designing effective digital marketing strategies that enhance product credibility, strengthen trust, and drive purchase conversions. The study recommends managing customer reviews and promotional activities consistently to boost platform credibility and foster consumer loyalty within Indonesia’s e-commerce ecosystem.